Extended S-parameters for imperfect test ports. (19th January 2015) - Hoffmann, J; Wollensack, M; Ruefenacht, J; Zeier, M
Abstract: Reflection and transmission of microwaves in coaxial devices are usually described by S-parameters. The current definition of S-parameters requires that the reference plane is in a section of ideal wave guide. Due to this, tremendous effort is necessary to facilitate the dissemination of standards, for the comparison of measurement values and for cascading devices. These processes can be simplified by extending the definition of S-parameters to reference planes in sections of non-ideal wave guide, e.g. in connectors. Extended S-parameters can be approximated with conventional simulation programs. Practical experiments show that extended S-parameters can be compared and cascaded without effort.